The role of local community institutions in managing capture fisheries resources in the coastal areas of Maros Regency - Daris, Lukman; Massiseng, Andi Nur Apung; Rochmady, Rochmady (Sangia Research Media and Publishing, 2022)
The research aims to determine the role of local community institutions in the management of capture fisheries resources in the coastal area of Maros Regency. The research strategy was a case study on fishing communities in the coastal area of Maros Regency from July 2022 to December 2022. Data were collected through in-depth interviews, observations, and document studies. The results showed that; the role of local community institutions in the management of capture fisheries resources, traditional local institutions (punggawa-sawi and nakasa') play a role as resource utilizers and conservationists, while local institutions are formed/modern (Pokmaswas) play a role in (1) conducting supervisory activities in resource utilization and conservation, (2) facilitating and assisting fishing communities in resource management, (3) coordinating resource management, and (4) reporting community activities that have the potential to damage the sustainability of capture fisheries resources.